Peran Kepala Sekolah dalam Pelaksanaan Manajemen Berbasis Sekolah di SD Negeri 12 Talang Ubi Pali Sumatera Selatan - Parasih; Sukirman; Asbiri; Saipul Annur; Ade Rosad (TAUJIH: Jurnal Pendidikan Islam, 2025)
Through the School-Based Management (SBM) policy, principals—as policy makers at the school level—can optimize all available resources to create a more effective and efficient educational process, particularly in the aspects of planning, implementation, and evaluation. However, In parctice, many school principals are still unable to fully implement SBM, resulting in minimal changes in school conditions and management. Therefore, this study aims to examine the role of the principal in the implementation of SBM at SD Negeri 12 Talang Ubi. This research adopts a qualitative approach using a descriptive method. Data analysis was conducted in three stages: (1) data reduction, (2) data display, and (3) conclusion drawing. Based on findings in the field, the principal has carried out his role professionally in implementing SBM. The principal acts as a role model and motivator for both teaching and administrative staff, and has taken the initiative to propose building renovations and procurement of educational facilities and infrastructure. The researcher concludes that the principal has performed well in leadership, motivating teachers, and improving infrastructure during the SBM implementation. It is recommended that the principal continue to enhance his professionalism to strengthen public recognition and trust in the educational institution.